Conditional eco-efficiency measure from the perspective of pollution emission firms. (18th July 2011) - Yang, Feng; Ang, Sheng; Liang, Liang; Zhai, Dujun
This paper proposes a conditional eco-efficiency measure with constraints to profit and pollution goals from the perspective of pollution emission firms. The measure is obtained not only by comparing the relative performance to other decision-making units (DMUs), but also by comparing the existing level relative to expected profit and pollution goals. We use the proposed measure to appraise the eco-efficiency of 32 paper mills along the Huai River in China, and discuss the sensitivity of eco-efficiency with some varying parameters. Different from the previous eco-efficiency measures, our technique admits the selfish motives of pollution emission firms which have little motivation to minimise the pollution emission. As a result, the current approach can be accepted by pollution emission firms for providing feasible strategies in performance improvement.